The Role of Teacher Personality Competence in Islamic Religious Education and Character Education Subjects for the Inculcation of Religious Character in Class VI B at Mojosongo III State Elementary School, Surakarta, Academic Year 2025/2026 - Amanda Nabilah Diyanto; Anita Trisiana; Muhammad Faruq Hanafi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to describe the role of personality competency of Islamic Religious Education and Character Building teachers in Surakarta for instilling religious character in class VI B students at SDN Mojosongo III Surakarta in the 2025/2026 academic year. This study uses a descriptive qualitative approach with a case study method. The subjects of this study were the Principal, Islamic Religious Teachers, and Class VI B Students. Data collection techniques in this study were through observation, interviews, and documentation. The method of checking the validity of qualitative data was carried out by triangulation of sources and triangulation of techniques. The data in this research technique were analyzed in the sequence of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that (1) the role of good teacher personality competency is able to play a role in instilling and developing religious character in class VI B students at SDN Mojosongo III Surakarta in Islamic Religious Education and Character Building learning, although there are still some student behaviors that need to be continuously fostered and improved through teacher habits and role models. (2) The implementation of Islamic Religious Education and Character Education in improving the religious character of class VI B students at Mojosongo III Surakarta State Elementary School is carried out through various learning activities that integrate religious values in the teaching and learning process. These activities include getting used to praying before and after activities, improving table manners such as praying before eating and drinking, eating and drinking while sitting, praying in congregation, as well as instilling attitudes of discipline, politeness, and respect for others.